University Dropout: A Systematic Review of the Main Determinant Factors (2020-2024) [version 2; peer review: 2 approved] - Juan Carlos Cárdenas Valverde; Vilma Inga Choque; Abraham Ccencho Pari; Javier Carrillo Cayllahua; Raul Quincho Apumayta; Delsio Huamán Ataypoma (F1000Research)
Introduction This research is a systematic review aimed at synthesizing scientific evidence on the causes of university dropout, focusing on the subcategories of vocational guidance, academic performance, socioeconomic status, and institutional aspects between 2020 and June 2024. Methods Only articles addressing university dropout were considered, analyzing dimensions such as vocational guidance, academic performance, socioeconomic status, and institutional aspects. Articles published in indexed scientific journals with double-blind, double-blind peer, or open reviews between 2020 and June 2024 were included. The main databases used were Scopus, Web of Science, and Google Scholar. To assess the risk of bias in qualitative studies, the criteria from the article “Validity criteria for qualitative research: three epistemological strands for the same purpose” were used. For quantitative studies, the criteria from the article “Evaluating survey research in articles published in Library Science journals” were followed. For mixed-method studies, both sets of criteria were combined. Results A total of 23 studies were included: 15 quantitative (65.22%), 3 qualitative (13.04%), and 5 mixed-method (21.74%). All studies (100%) addressed the subcategories of socioeconomic status and institutional aspects. Regarding the academic performance subcategory, 86% of the studies addressed it, while the vocational guidance subcategory was covered by 73.91% of the studies. Conclusions Vocational guidance, academic performance, socioeconomic status, and institutional aspects are crucial for reducing university dropout. Providing adequate professional guidance, academic support, financial assistance, and strong institutional support is fundamental to improving student retention and academic success.